2017
DOI: 10.1186/s12967-017-1291-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Semmes–Weinstein monofilament test results are associated with oxidative stress markers in type 2 diabetic subjects

Abstract: BackgroundDifferent lines of evidence suggest that oxidative stress (OS) is implicated in the pathogenesis of diabetic neuropathy. The Semmes–Weinstein monofilament (SWM) test is an efficient tool for evaluating diabetic polyneuropathy and diabetic foot. In this study, we analyzed the association between OS markers and altered SWM test results in type 2 diabetes (T2DM) patients.MethodsSeventy T2DM patients were studied and 34 showed altered SWM results. The clinical and biochemical parameters were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the present study, the diagnosis of polyneuropathy was based on the response to the monofilament test as it has already been published by our group and reported previously in the literature [21,26,27]. Lee et al [28] described a sensitivity of 93% and a specificity of 100% when performing a ten-points monofilament examination and comparing it to nerve conduction studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present study, the diagnosis of polyneuropathy was based on the response to the monofilament test as it has already been published by our group and reported previously in the literature [21,26,27]. Lee et al [28] described a sensitivity of 93% and a specificity of 100% when performing a ten-points monofilament examination and comparing it to nerve conduction studies.…”
Section: Discussionmentioning
confidence: 88%
“…The criteria used to make the diagnosis of DPN has been described previously [21]. DPN was established through the Semmes-Weinstein test (SW) by applying 10 g of force with a 5.07-gauge monofilament [22].…”
Section: Diagnosis Of Dpnmentioning
confidence: 99%
“…Aziza (2014) found that an increase of MDA serum level in diabetic neuropathy rats [22]. Martinez-Hevaz (2017) reported that altered in MDA values is associated with polyneuropathy in diabetic patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…A physical examination including vital tests such as patient’s blood pressure and anthropometrical data such the body mass index and abdominal circumference was performed using standardised methods 21 . Ankle‐brachial index (ABI) was obtained using a protocolised method calculating the ratio between the ankle systolic pressure and the brachial systolic pressure measured with a mercury sphygmomanometer and a Doppler ultrasound (Bi‐directional Smartdop 20) after 5‐10 minutes of rest.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria used to make the diagnosis of DPN have been described previously 21 . DPN was established through the Semmes‐Weinstein test (SW) by applying 10 g of force with a 5.07‐gauge monofilament 22 .…”
Section: Methodsmentioning
confidence: 99%